n-Digit Benford Converges to Benford - Azar Khosravani; Constantin Rasinariu (International Journal of Mathematics and Mathematical Sciences)
Using the sum invariance property of Benford random variables, we prove that an n-digit Benford variable converges to a Benford variable as n approaches infinity.